Integrating Gender Into Data Services: A Flexible, Multidisciplinary and Reflexive Approach - Kadel, Lalu Maya; Chitale, Vishwas Sudhir; Gurung, Kamala (Frontiers in Climate, 2022)
Drawing on the concepts of Theory of Change and Participatory Impact Pathways Analysis, and our own experience of integrating gender and social inclusion in the Community Resilience Forest Management System in Nepal, we develop a five-step framework, which we call flexible, multidisciplinary and reflexive (FMR) approach to mainstreaming gender and social inclusion in the given context of data services. In this study, we demonstrate how this newly devised concept can be effectively implemented at different project stages—planning, monitoring and evaluation—to integrate gender and social inclusion in data services. As reflected in a Climate Resilient Forest Management System in Nepal, we present how the project has successfully harnessed an approach that has transformed a project team, improved understanding of the interface between the two disciplines and helped integrate gender and social inclusion in data services. This study contributes to many ongoing discussions and debates within academic literature about interdisciplinary research projects, and the integration of gender and social inclusion particularly into climate related research and data services.